A review of NARES-IARC-Donor collaboration to develop demand-driven technologies for improved maize production in West and Central Africa - Fakorede, M.A.B.; Badu-Apraku, Baffour; Menkir, A.; Ajala, S.O.; Lum, A.F. (International Institute of Tropical Agriculture, 2007)
Maize researchers in West and Central Africa (WCA) established the West and Central Africa Collaborative Maize Research Network (WECAMAN) in 1987 to tackle maize production constraints too formidable for individual national programs to overcome. The National Agricultural Research Systems (NARS) that were relatively strong for specific research areas were funded by the Network to generate improved technologies, which were evaluated in on-farm trials and adopted or adapted in other member countries of the Network. The Network allocated funds for research and other activities to member countries through competitive grants. USAID has been the major funding agency of WECAMAN since inception. In recent years, aditional funding support came from IFAD and UNDP through the Africa Maize Stress Project, the Nippon Foundation QPM Project, and the HarvestPlus Challenge Program. The NARS of WCA provided research and development infrastructure, staff salaries, and logistics for research. International agricultural research centers, specifically, IITA and CIMMYT, have been providing the required source germplasm. IITA has been the executing agency of the Network since inception and has also provided advanced laboratory and other necessary research support facilities and experienced scientists for expert consultation, as necessary. The Network made major breakthroughs during the period under review by generating and transferring to farmers improved maize production technologies. Maize production increased in the traditional maize belts and was extended to new areas. Average productivity of maize increased by about 30% while total grain production in the region increased by nearly 400% during the two decades of WECAMAN's existence. Other benefits derived from the Network were improved research capacity of the NARS and capability of the research technicians and scientists, better research-extension-farmer linkage, improved research management and communication skills of the scientists and improved interpersonal relationships, with enhanced trust and confidence among maize scientists in the subregion. WECAMAN's success has resulted from the effective and efficient collaboration of the three major players, the NARS, IARCs, and donors.